The plant contract : art's return to vegetal life - Gibson, Prudence (Critical plant studies, 2018)
The Plant Contract argues that visual and performance art can help change our perception of the vegetal world, and can return us to nature and thought. Via an investigation into the wasteland, robotany, feminist plants, and nature rights, this phytology-love story investigates how contemporary art is mediating the effects of plant-blindness, caused by human disassociation from the natural world. It is also a gesture of respect for the genius of vegetal life, where new science proves plants can learn, communicate, remember, make decisions, and associate. Art is a litmus test for how climate change affects human perception. This book responds to that test by expressing plant-philosophy to a wider public, through an interrogation of plant-art.